Heterosexual Risk for HIV Among Puerto Rican Women: Does Power Influence Self-Protective Behavior? - Saul, Janet (2000)
Lack of power in relationships has been offered as an explanation for why women do not always engage in safer sex behavior with male partners. However, few studies have empirically tested the association between power and self-protective behavior. Causal modeling procedures were used to examine the interrelations of seven measures of power and to examine the effects of power on women’s HIV-related communication and condom use with male partners. Power was measured by education, employment, decision making, perceived alternatives to the relationship, commitment to the relationship, investment in the relationship, and absence of abuse in the relationship. The sample comprised 187 Puerto Rican women, aged 18–35 years, attending a comprehensive health clinic in the Bronx, New York, who were at risk for heterosexual transmission of HIV. Women who were currently employed and those who were more committed to their relationships reported less HIV-related communication. Condom use was predicted by shorter length of the relationship, more education, current employment, less investment in the relationship, and more HIV-related communication.